Mining conflict in santa ana (Puno) - Pinto Herrera, Honorio (2013)
The paper addresses the mining conflict in Santa Ana (Puno) occurred in the first half of 2011. Describes the geographic and project owner. It also studies the origins of the conflict between authorities and residents of the districts of Huacullani and Kelluyo and the Canadian company Bear Greek. The test can show that the main causes of the conflict are the way in which the company acquires the concession and clientelistic relations established with some communities and partnerships with certain political actors between the state, business and communities also on environmental impact study, and finally there is an account of the major events that occur between the start of the indefinite strike until the final outcome of it.